Lafora Disease: A Case Report of Progressive Myoclonic Epilepsy - Sahar Delavari; Sogol Olamazadeh; Nima Ameli; Bahareh Pourghaz; Abbas Tafakhori (Case Reports in Clinical Practice, 2023)
Lafora disease is a rare genetic disease caused by the accumulation of malformed glycogen products in the tissues. The disease usually manifests with idiopathic generalized tonic colonic seizures with poor response to antiepileptic drugs (AEDs). We report the case of a 19-year-old girl with the chief complaint of generalized refractory seizures, jerky movement, and cognitive deterioration with a positive history of epilepsy in her younger brother. The disease onset was at the age of 16 with jerky movement and blurred vision. She was admitted to our ward to have a long-term video EEG monitoring for further evaluation. Clinical presentation accompanied with abnormal EEG characteristics for Lafora disease, and the positive familial history were highly suggestive of Lafora disease. The disease was confirmed with genetic testing by which the mutation of EPM2A was detected.